2023
DOI: 10.11591/ijeecs.v29.i3.pp1817-1826
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis of Malayalam tweets using bidirectional encoder representations from transformers: a study

Abstract: Sentiment analysis on views and opinions expressed in Indian regional languages has become the current focus of research. But, compared to a globally accepted language like English, research on sentiment analysis in Indian regional languages like Malayalam are very low. One of the major hindrances is the lack of publicly available Malayalam datasets. This work focuses on building a Malayalam dataset for facilitating sentiment analysis on Malayalam texts and studying the efficiency of a pre-trained deep learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…By focusing on sentiment analysis, the research seeks to uncover and understand the emotional aspects conveyed within Malayalam text data [5]. In paper [6] Yoon presented an innovative real-time recommenda-tion system for tourism, named R2Tour, designed to adapt to dynamic scenarios, including external factors and distance information, providing personalized recommendations for tourists based on their preferences and characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By focusing on sentiment analysis, the research seeks to uncover and understand the emotional aspects conveyed within Malayalam text data [5]. In paper [6] Yoon presented an innovative real-time recommenda-tion system for tourism, named R2Tour, designed to adapt to dynamic scenarios, including external factors and distance information, providing personalized recommendations for tourists based on their preferences and characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Paper [7] proposes a novel approach that leverages deep learning techniques within the context of global information management to provide personalized travel recommendations for different users by utilizing deep learning models and the system can effectively analyse and interpret large-scale global information, including user preferences, location data, and cultural factors, to generate tailored recommendations. Mahadevaswamy proposed a technical overview of a Bidirectional LSTM network for Sentiment Analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Elankath and Ramamirtham [9] examined the efficiency of using the BERT model for sentiment analysis on a Malayalam dataset constructed from 2,000 tweets from 𝕏. They found that BERT outperforms other machine learning (ML) and deep learning (DL) models with an accuracy of 88.61%.…”
Section: Introductionmentioning
confidence: 99%